Development of Basic Locomotor Movements in Elementary Schools Through Runthojump (Run Throw And Jump) Games - Danar Wahyu Aji; Suyatmin (Universitas Negeri Semarang, 2026)
Physical education in elementary schools plays an important role in developing students' motor skills, attitudes, and character through meaningful physical activities. The teaching of basic locomotor movements in elementary schools is still dominated by conventional methods, which are less interesting and result in low motivation and engagement among students. Based on observations and interviews at MIS Ath-Thalibin, students showed high enthusiasm when learning was conducted using a play-based approach, but the variety of games used was still limited and not systematically integrated. This study aims to develop the RUNTHOJUMP (Run, Throw, and Jump) game, which is packaged in a teaching module as an alternative innovative learning method to improve the basic locomotor skills of elementary school students in phase B. This study uses the Research and Development (R&D) method with a 4D development model that includes the define, design, develop, and disseminate stages. The research subjects consisted of 19 phase B elementary school students. Data analysis techniques were performed descriptively, qualitatively, and quantitatively. Qualitative analysis was used to process criticism and suggestions from experts, while quantitative analysis was performed through validation using a Likert scale to determine the product's feasibility level. The results showed that the RUNTHOJUMP teaching module developed was valid based on the assessment of experts in terms of material, media, and practicality. The RUNTHOJUMP game can be used as an alternative learning approach to support the development of basic locomotor skills in elementary school students and to enhance student engagement in physical education learning.